2018
DOI: 10.1039/c7ra11495h
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of coal fly ash in copper ion adsorption followed by thermal stabilization in a spinel solid solution

Abstract: Coal fly ash is usually used as a cost-effective adsorbent for heavy metal removal, accumulating large amounts of spent coal fly ash that requires further disposal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Furthermore, the larger amount of spectral features in the EUFA XRD spectrum shown in Figure 1 indicates a much more complex mineralogy, including compounds such as ZnO and copper species such as CuO, Cu 2 O, and Cu 2 S. These species are commonly present in FA samples but in different proportions depending on its source region and the combustion process. 55,56 The presence of copper(I), as for iron(II), in EUFA is mostly the result of an incomplete combustion process characteristic of this sample. Furthermore, copper AAS analysis of all FA samples showed that EUFA contains (720 ± 10) μg g −1 of Cu, about 5 times more than USFA and 36 times more than INFA.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Furthermore, the larger amount of spectral features in the EUFA XRD spectrum shown in Figure 1 indicates a much more complex mineralogy, including compounds such as ZnO and copper species such as CuO, Cu 2 O, and Cu 2 S. These species are commonly present in FA samples but in different proportions depending on its source region and the combustion process. 55,56 The presence of copper(I), as for iron(II), in EUFA is mostly the result of an incomplete combustion process characteristic of this sample. Furthermore, copper AAS analysis of all FA samples showed that EUFA contains (720 ± 10) μg g −1 of Cu, about 5 times more than USFA and 36 times more than INFA.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…According to the presented data, the FA exhibits adsorption capacity for Cu(II) ions equal to 27.32-58.48 mg/g [25]. Wu et al presented the maximum adsorption capacity for Cu(II) at the level of 48.8 mg/g [26]. Kumar et al analyzed the possibility of removal of Cd(II), Ni(II), Cu(II) in aqueous systems.…”
Section: Introductionmentioning
confidence: 98%